Experienced golfers` perspectives on choking under pressure - Gucciardi, D. F.; Longbottom, J. -L.; Jackson, B.; Dimmock, J. A. (Journal of Sport & Exercise Psychology, 2010)
Although researchers have experimentally examined the mechanisms underlying pressure-induced forms of suboptimal performance, or "choking under pressure," there is a lack of research exploring the personal experience of this phenomenon. In an attempt to fill this void in the literature, this study explored experienced golfers` perceptions of the choking experience within a personal construct psychology (Kelly, 1955/1991) framework. Both male and female golfers participated in either a focus group (n = 12; all males) or one-on-one interview (n = 10; female = 7, male = 3) using experience cycle methodology (Oades & Viney, 2000) to describe their perceptions of the choking experience. Discussions were transcribed verbatim and subsequently analyzed using grounded theory analytical techniques (Strauss & Corbin, 1998). Analyses revealed five central categories representing the personal experience of choking under pressure: antecedents, personal investment, choking event, consequences, and learning experiences. The findings reported here suggest that the choking phenomenon, which can involve acute or chronic bouts of suboptimal performance (relative to the performance expectations of the athlete), is a complex process involving the interplay of several cognitive, attentional, emotional, and situational factors. Implications of the findings for a construct definition of choking are discussed, and several applied considerations are offered.